Tahliil Mawaad al-Tadriibaat wa Ikhtibaraat Mahaarah al-Istimaa’ fii Ta’liim al-Lughah al-Arabiyah bi al-Madrasah al-Ibtidaaiyyah - Bastian, Achmad Fandi; Munir, Muhammad Mubasysyir (Lugawiyyat, 2023)
Basic language skills include four skills: listening, speaking, reading, and writing. Listening is one of the four language abilities taught in elementary schools. However, Arabic textbooks in elementary schools using K13 have not been maximized in providing part of the training materials in listening skills. This paper attempts to explore the materials for listening skills exercises and tests in the textbook using K13 in elementary schools. The purpose of the study was to describe the exercises and tests of listening skills in the textbook. The methodology used in this study is qualitative research methodology with content analysis, and the data sources are the textbook using K13 in elementary school. The results of this study showed that the Arabic language material practiced by the listening skill in this book is insufficient and does not yet represent the purpose of teaching the listening skill specifically, as it was the purpose of teaching the communicative Arabic language announced in generallaw. The materials for the Arabic listening skills tests in this book are not well prepared, they are not written within the book, and the test is conducted by the teacher on his initiative and needs